The Effectiveness Of The Distribution Of Zakat Funds In The Bali Makmur Program In Improving Mustahik Welfare In Baznas Bali Province - Rachid Gunawan Wibisono; R. Agrosamdhyo2, Kurniawati (Harmony Philosophy: International Journal of Islamic Religious Studies and Sharia, 2024)
Over time, BAZNAS has become one of the important institutions in the management of zakat in Indonesia, by increasing efficiency, transparency, and effectiveness in managing zakat, as well as distributing it to those in need. Therefore, the effectiveness of the distribution of zakat funds in the Bali Makmur Program at BAZNAS Bali Province plays an important role. This study aims to understand the effectiveness of the distribution of zakat funds in the Bali Makmur Program in improving the welfare of mustahik in BAZNAS Bali Province. The focus of this research; 1) What is the form of distribution of zakat funds in the Bali Makmur Program at BAZNAS Bali Province?, 2) What is the effectiveness of the distribution of zakat funds in the Bali Makmur Program in improving the welfare of mustahik in BAZNAS Bali Province? and 3) What are the obstacles in the distribution of zakat funds in the Bali Makmur Program at BAZNAS Bali Province? The objectives of this study are; 1) To find out the form of distribution of zakat funds in the Bali Makmur Program.2) To identify the effectiveness of the Bali Makmur Program in improving the welfare of mustahik in the city of Denpasar Bali and 3) To find out the obstacles faced in the distribution of zakat funds in the Bali Makmur Program. The research method to be used is qualitative descriptive, with data collection techniques through observation, interviews, and documentation, as well as data validity techniques through the triangulation method. Determination of informants by purposive sampling technique. The results of the research will be described in a descriptive manner.